THE COMPARATIVE IMPACT OF JUTE LEAF AND UTAZI LEAF ETHANOLIC EXTRACT ON THE ESSENTIAL AMINO ACID PROFILE OF Clarias gariepinus FINGERLINGS EXPOSED TO DICLOFENAC - Okoh, Emmanuel Chidera; Orji, Alexander Emeka; Ude, Wilson Chukwuemerie, (Global Journal of Chemistry, Biology and Physics (GJCBP), 2025)
This study investigated the comparative impact of jute leaf (Corchorus olitorius) and utazi leaf (Gongronema latifolium) ethanolic extracts on the essential amino acid profile of Clarias gariepinus fingerlings treated with diclofenac. Diclofenac, a widely used pharmaceutical, has been shown to disrupt amino acid metabolism in aquatic organisms, leading to reduced growth and compromised health. This study aimed to evaluate the protective effects of jute and utazi leaf extracts on these adverse effects. Fingerlings were exposed to diclofenac and treated with either jute or utazi leaf extract. The result of the phytochemical analysis of jute leaf showed that tannins, saponin, and flavonoids had high ethanol constituent (10mg/100g, 9.4mg/100g, and 7.24mg/100g respectively), while the phytochemical analysis of utazi leaf showed that tannins, quinones, and flavonoids had high ethanol constituent (10mg/100g, 9.4mg/100g, and 7.24mg/100g respectively). The results indicated that both extracts significantly improved the essential amino acid profile, with jute leaf extract showing a pronounced effect on lysine and methionine levels (9.50±0.04 and 4.13±0.04 after 28 days), while utazi leaf extract had a broader impact on multiple amino acids, such as methionine, phenylalanine, histidine, arginine, and tryptophan, (8.59±0.04, 9.40±0.04, 9.70±0.04, 6.27±0.04, and 8.51±0.04 respectively after 28 days). These findings suggest that both plant extracts are effective mitigative agents against diclofenac-induced amino acid depletion in aquaculture. This study highlights the potential of phytochemical-rich plant extracts to enhance fish health and productivity in contaminated environments